Results of the field surveys at Teos and environs (2007–2009): revealing the Archaic landscape - Koparal, Elif; Tuna, Numan (Journal of Greek Archaeology, 2017)
Teos is one of the Ionian dodecapolis cities located on the western coast of Anatolia (Figure 1). It is visually one of the most favourable sites with its monumental buildings and post-classical urban layout well preserved within its landscape. Including Teos, the imagination stirred by Ionian poleis is mostly of an urban centre and its monuments, particularly the temples. At most places in Ionia post-Archaic urban structures seal up the earlier layers of habitation, which has been an obstacle for a long dureé approach, and a consequence of the preferred research strategies. Archaeological practice in Ionia has long been focused on the excavation of temples and monumental buildings, which contributed to the macro history of the region as presented by the ancient authors.